Pan-Africanism in the Academia : John Henrik Clarke and the African Heritage Studies Association - Pauline Guedj (Nuevo mundo - Mundos Nuevos, 2016)
At the 1969 African Studies Association meeting in Montreal, a group of Black intellectuals, challenged the « neocolonial functioning » of the organization and pressed for greater Black representation within its leadership. The conflict gave rise to the African Heritage Studies Association, which, under the leadership of John Henrik Clarke, organized meetings as well as transnational networks of Black studies scholars. For many contemporary historians, the 1969 founding of AHSA represents the first manifesto of « Afrocentrism » within North American academic circles. It is thought of as a first attempt to consciously « racialize » social sciences and to claim for the reconstruction of African history along what John Henrik Clarke already called « afrocentric » lines. Based on an ongoing research on African American academic activism, this paper will argue that beyond « Afrocentrism », what the members of AHSA were trying to create was a Pan-African organization grounded in politics and anticolonial struggle. In their view, the rewriting of African history was a first step toward a broader revolution that could affect power relations in the United States and build a united Pan-African community.